PENGARUH PENGGUNAAN EUCHEUMA COTTONII SEBAGAI IMUNOSTIMULAN PADA BIDANG AKUAKULTUR (REVIEW) - MUAHIDDAH, NURI; ASRI, YULIANA (GANEC SWARA, 2024)
Eucheuma cottonii has been extensively studied in the field of aquaculture due to its potential as a natural immunostimulant. In this review, we explore the impact of using Eucheuma cottonii as an immunostimulant in aquatic animals. Based on recent literature, we conclude that Eucheuma cottonii can enhance the immune response in aquatic organisms, including increasing Total Haemocyte Count, phagocytic activity, and gene expression related to the immune system, thus enabling aquatic organisms to combat bacterial and viral infections. The mechanism of action of Eucheuma cottonii is believed to involve bioactive compounds such as sulfated polysaccharides that stimulate non-specific immune responses. The implications of using Eucheuma cottonii in aquaculture include the potential to improve the health and production performance of aquatic animals. However, challenges such as quality control of extracts, interspecies effectiveness, and potential environmental risks need to be addressed. Suggestions for further research include a deeper understanding of the mechanism of action, comparative studies among species, development of production technologies, environmental risk management, as well as education and training for aquaculture farmers. With careful and sustainable approaches, the use of Eucheuma cottonii as an immunostimulant has the potential to enhance the sustainability of the aquaculture industry and the overall health of aquatic animals.